LINC00626 drives tamoxifen resistance in breast cancer cells by interaction with UPF1 - Hui Yuan; Lianbang Zhou; Wei Hu; Min Yang (Scientific Reports)
Abstract Although tamoxifen is commonly utilized as adjuvant therapy for Estrogen Receptor alpha (ERα)-positive breast cancer patients, approximately 30–50% of individuals treated with tamoxifen experience relapse. Therefore, it is essential to investigate additional factors besides ERα that influence the estrogen response. In this study, cross-analysis of databases were performed, and the results revealed a significant association between LINC00626 and ERα signaling as well as increased expression levels of this gene in tamoxifen-resistant cells. LINC00626 is a novel ERα-regulated long non-coding RNA (lncRNA) that has not yet been examined for its potential contribution to endocrine therapy resistance. This study revealed that the upregulation of LINC00626 in breast cancer was associated with poor overall survival in patients. Additionally, ERα signaling was found to transcriptionally regulate LINC00626 expression, thereby promoting cancer progression and enhancing resistance to tamoxifen in breast cancer cells via the regulation of UPF1 expression. Depletion of LINC00626 restored sensitivity to tamoxifen by activating the PERK-ATF4-CHOP signaling pathway via UPF1. These findings support the role of LINC00626 as a potential therapeutic target for combating tamoxifen resistance.